A hybrid randomized algorithm for image compression - Mehrdoust, Farshid (International Journal of Applied Mathematical Research, 2012)
In this paper, we present a randomized algorithm for image compression by improving the Markov chain Monte Carlo algorithm and by applying the principal component analysis method. Some Numerical examples are provided to show that the proposed algorithm is effective.